Design, characterization, and electromagnetic performance of a flexible wideband RF antenna using composite materials - Eddiai, Adil; Al Gburi, Ahmed Jamal Abdullah; Douhi, Saïd; Labihi, Salesabil; Lakrit, Soufian; El Achaby, Mounir (Elsevier B.V., 2025)
Traditional microwave and microelectronic technologies typically use metal components for high efficiency, but their rigidity and susceptibility to corrosion limit their suitability for wearable applications. To meet the demand for flexible, high-performance materials in wearable communication systems, this study investigates the use of Poly (vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) combined with calcium- and zirconium-doped barium titanate (BCZT) as a novel substrate for microwave applications. A flexible wideband antenna was developed using a PVDF-HFP/BCZT composite, with BCZT particles enhancing the composite’s thermal stability, crystallinity, and dielectric performance. Conductive fabric was employed for the antenna’s radiating elements, supporting both flexibility and user comfort. The antenna was fabricated via laser cutting and tested in free space and on a human body model, achieving a resonant frequency of 5.94 GHz, a return loss of − 48.32 dB, and a wide bandwidth of 5.10–6.40 GHz, with VSWR below 2 and a radiation efficiency of 60%. Specific absorption rate (SAR) testing with a multilayer human tissue model yielded values of 1.22 W/kg (1g) and 0.366 W/kg (10g), in compliance with international safety standards. Experimental results closely aligned with simulations, demonstrating the potential of PVDF-HFP/BCZT-based antennas as eco-friendly, high-performance solutions for wearable technologies, achieving an effective balance between flexibility and efficiency.